Temperature-dependent polarity reversal in Au/TlGaSe2 Schottky junctions - Seyidov, MirHasan Yu.; Suleymanov, Rauf A.; Bakis, Yakup (Amer Inst Physics, 2009)
Temperature-dependent reversal of the rectifying polarity has been observed in Au/TlGaSe2 Schottky junctions. To explain the experimental findings the important role of the tunneling current was taken into account. Besides, it was found that the temperature range, where the rectifying polarity reversal is observed, coincides with the temperature interval where an electronic phase transition takes place in TlGaSe2 crystals. The interface permittivity is significantly changed as a result of phase transitions, thus changing the Schottky barrier's width and consequently the contributions of tunneling and usual thermally assisted transitions. Schottky barrier method becomes a powerful tool investigating phase transitions in semiconductors.
Keywords: gallium compounds; permittivity; phase transformations; rectification; Schottky barriers; semiconductor-metal boundaries; ternary semiconductors